Factors influencing choice of chemotherapy in metastatic colorectal cancer (mCRC) - Rossi L; Vakiarou F; Zoratto F; Bianchi L; Papa A; Basso E; Verrico M; Lo Russo G; Evangelista S; Rinaldi G; Perrone-Congedi F; Spinelli GP; et al. (Cancer Management and Research, 2013)
Luigi Rossi, Foteini Vakiarou, Federica Zoratto, Loredana Bianchi, Anselmo Papa, Enrico Basso, Monica Verrico, Giuseppe Lo Russo, Salvatore Evangelista, Guilia Rinaldi, Francesca Perrone-Congedi, Gian Paolo Spinelli, Valeria Stati, Davide Caruso, Alessandra Prete, Silverio TomaoDepartment of Medico-Surgical Sciences and Biotechnologies, "Sapienza" University of Rome, Rome, Italy; Oncology Unit, ICOT, Latina, ItalyAbstract: Management of metastatic colorectal cancer requires a multimodal approach and must be performed by an experienced, multidisciplinary expert team. The optimal choice of the individual treatment modality, according to disease localization and extent, tumor biology, and patient clinical characteristics, will be one that can maintain quality of life and long-term survival, and even cure selected patients. This review is an overview of the different therapeutic approaches available in metastatic colorectal cancer, for the purpose of defining personalized therapeutic algorithms according to tumor biology and patient clinical features.Keywords: metastatic colorectal cancer, patient clinical features, tumor biology, multidisciplinary approach